MODERN DESIGN TECHNOLOGIES OF THE SCIENTIFIC RESEARCH AND EDUCATIONAL CENTER OF THE NATIONAL INDUSTRIES - LOHINOV чANTON; PARASKA, OLGA; YATSENKO, VIKTOR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article proposes modern technologies and develops conceptual approaches to the design of a research and educational center that ensure functionality and compliance with historical traditions. The main planning zones and functions of the complex have been determined, including administrative, educational, research, craft, exhibition and recreational zones, ensuring the effective use of the territory and promoting the popularization of folk crafts. In order to form the conceptual foundations, the comparative historical method was used in the study in order to evaluate the organization of places in the past and integrate them into the present. In the 19th century, landlord settlements were a key component of the socio-economic structure on the territory of Ukraine. The analysis of folk crafts and their integration at the cultural heritage site allows for the implementation of a cultural program for visitors, namely: various workshops in weaving, pottery, cheese making, baking, woodworking, as well as holding folk holidays and ceremonies. An important part of the cultural program are folklore performances and theatrical productions, which contribute to the preservation of Ukrainian culture. Planning solutions have been developed that take into account the characteristics of historic buildings and the landscape, including strengthening the banks, installing drainage systems and other engineering measures to ensure the stability, sustainability and safety of the complex. The project of the research and training center of folk crafts in the village of Sednіv (Chernihiv region) is an important step in preserving the cultural heritage of Ukraine. It will contribute to the economic growth of the region and sustainable development, the development of tourism, raising the level of public awareness of folk crafts and traditions.